Analysis of the screening and predicting characteristics of the house-tree-person drawing test for mental disorders: A systematic review and meta-analysis - Guo, Huibing; Feng, Bin; Ma, Yingqiao; Zhang, Xueyi; Fan, Huiyong; Dong, Zaiquan; Chen, Taolin; Gong, Qiyong (Frontiers in Psychiatry, 2023)
Background The house-tree-person (HTP) drawing test has received growing attention from researchers as a common projective test. However, the methods used to select and interpret drawing indicators still lack uniformity. Objective This study aims to integrate drawing indicators into the process of screening for or classifying mental disorders by conducting a systematic review and meta-analysis of the application of the HTP test. Methods A search of the following electronic databases was performed in May 2022: PubMed, Web of Science, Embase, EBSCO, CNKI, VIP, and Wanfang. Screening and checking of the literature were performed independently by two researchers. The empirical studies published on the use of the HTP test in mental disorders and studies providing specific data on the occurrence frequency of drawing characteristics were analyzed. A total of 30 studies were included in the meta-analysis, including 665 independent effect sizes and 6,295 participants. The strength of the association between drawing characteristics of the HTP test and the prevalence of mental disorders was measured by the ratio (OR) with a 95% CI. Publication bias was assessed using a funnel plot, Rosenthal’s fail-safe number (Nfs), and the trim and fill method. Results The results revealed 50 drawing characteristics that appeared at least three times in previous studies, of which 39 were able to significantly predict mental disorders. The HTP test can be divided into the following four dimensions: house, tree, person, and the whole. These dimensions reflect the structure, size, and other characteristics of the picture. The results showed that the greatest predictor of mental disorders was the whole (OR = 4.20, p < 0.001), followed by the house (OR = 3.95, p < 0.001), the tree (OR = 2.70, p < 0.001), and the person (OR = 2.16, p < 0.001). The valid predictors can be categorized into the following four types: item absence, bizarre or twisted, excessive details, and small or simplified. The subgroup analysis showed that the affective-specific indicators included no motion, leaning house, and decorated roof; thought-specific indicators included excessive separation among items, no window, loss of facial features, and inappropriate body proportions; and common indicators of mental disorders included no additional decoration, simplified drawing, very small house, two-dimensional house, and very small tree. Conclusion These findings can promote the standardization of the HTP test and provide a theoretical reference for the screening and clinical diagnosis of mental disorders.